Social mobility in China: A case study of a quantitative sociological approach to social mobility research in the Global South - Yaojun Li (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This study analyses intergenerational class mobility in China as a case study of a quantitative sociological approach to social mobility research in the Global South. Drawing on national representative surveys collected between 2010 and 2015 in China, the analysis focuses on absolute and relative mobility rates for men and women across four birth cohorts. With regard to absolute mobility, we find rising levels of mobility, with upward mobility prevailing over downward mobility. With regard to relative mobility, we find constancy for the older cohorts but a growing rigidity for the youngest cohort of men. The urban-rural divide is increasingly blurred, but class differences are becoming more salient, especially between the professional-managerial salariat and the rest of society in occupational and educational attainment.
Keywords: 330; social mobility; hukou; education; gender; log-linear models; symmetrical odds ratios; China